2006
DOI: 10.1161/circulationaha.105.580506
|View full text |Cite
|
Sign up to set email alerts
|

Renal Function as a Predictor of Outcome in a Broad Spectrum of Patients With Heart Failure

Abstract: Background— Decreased renal function has been found to be an independent risk factor for cardiovascular outcomes in patients with chronic heart failure (CHF) with markedly reduced left ventricular ejection fraction (LVEF). The aim of this analysis was to evaluate the prognostic importance of renal function in a broader spectrum of patients with CHF. Methods and Results— The Candesartan in Heart Failure:Assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
486
4
18

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 827 publications
(532 citation statements)
references
References 38 publications
24
486
4
18
Order By: Relevance
“…Cardiorenal syndrome, a condition in which renal impairment occurs as a result of cardiac dysfunction, is associated with an increased risk of hospitalization and death 2, 3. Indeed, renal dysfunction is a stronger predictor of mortality than New York Heart Association (NYHA) functional class or left ventricular ejection fraction 4…”
mentioning
confidence: 99%
“…Cardiorenal syndrome, a condition in which renal impairment occurs as a result of cardiac dysfunction, is associated with an increased risk of hospitalization and death 2, 3. Indeed, renal dysfunction is a stronger predictor of mortality than New York Heart Association (NYHA) functional class or left ventricular ejection fraction 4…”
mentioning
confidence: 99%
“…We have shown that the prognostic value of ΔHR is independent of established markers of HF severity, in particular eGFR 13. Furthermore, the subgroup analysis suggested that ΔHR is modifiable and that its changes over time are also associated with prognosis.…”
Section: Discussionmentioning
confidence: 76%
“…In a study of 754 heart failure patients, survival was significantly tied to renal insufficiency with increased mortality associated with worsening renal dysfunction ( P  = 0.002) 16. Additionally, reduced GFR was associated with an increased risk of cardiovascular death and heart failure hospitalizations in 2680 North American patients with systolic and DD 17. Our study supports these findings and expands on these results by demonstrating that the presence of DD was associated with worse long‐term outcomes independent of renal function.…”
Section: Discussionmentioning
confidence: 99%